Technical feasibility of a 1000 MWe pulverized coal power plant under ammonia co-combustion conditions - Seung Seok Oh; Jester Lih Jie Ling; Hyun Jun Park; Han Saem Park; Ha Eun Lee; See Hoon Lee (Case Studies in Thermal Engineering, 2024)
Ammonia has attracted the attention as a practical way to reach carbon free power generation. Ammonia co-combustion characteristics in 1000MWe pulverized coal power plant was simulated by using Aspen Plus and evaluated under an excess air ratio of 1.0–1.2, air of 2642–3457 ton/hr, coal of 208.2–355.5 ton/hr, ammonia of 0–186.14 ton/hr and various coals. The influence of co-combustion ratios of different coals on emission characteristics and net efficiency was compared. For carbon dioxide emission reduction, the respective CO2 intensity reduction for KPU and BG was 36.44 and 37.76% in calorific value basis, 32.51 and 31.90% in weight basis. The net efficiencies of the power cycle showed a lower decrease as the fuel was supplied on the weight basis compared to the calorific value basis. Based on the obtained results, the KPU on the weight basis showed the lowest net efficiency decrement of 3.1%, but in terms of CO2 intensity reduction, BG on calorific value basis showed most drastic reduction of 37.76%. Consequently, these results showed an effective carbon reduction with ammonia co-combustion and provides a promising solution for the pulverized coal power plants to compass a meaningful reduction of carbon emissions and conservation of combustion efficiency.